Data and code for "Terrestrial water cycle acceleration-deceleration: Non-binary and space-time divergent" - Daniel Althoff; Georgia Destouni (Stockholm University, 2022)
This dataset provides all data compiled and generated for the manuscript entitled "Terrestrial water cycle acceleration-deceleration: Non-binary and space-time divergent" (manuscript under consideration). This includes the boundaries for 3614 hydrological catchments, the curated data used for analysis and modelling, the developed machine learning model, shapley values and area of applicability results, and data for global extrapolation

It also contains the code in a Quarto file ('Code.qmd') and a markdown file ('Code.html') which shows how to access and use the data, and generic sample codes used to generate these results.

Code - R session info:

R version 4.2.1 (2022-06-23 ucrt)

Platform: x86_64-w64-mingw32/x64 (64-bit)

Running under: Windows 10 x64 (build 22621)

Matrix products: default locale: [1] LC_COLLATE=Portuguese_Brazil.utf8 LC_CTYPE=Portuguese_Brazil.utf8 [3] LC_MONETARY=Portuguese_Brazil.utf8 LC_NUMERIC=C [5] LC_TIME=Portuguese_Brazil.utf8

attached base packages: [1] stats [2] graphics [3] grDevices [4] utils [5] datasets [6] methods [7] base

other attached packages: [1] bundle_0.0.0.9200 [2] stacks_1.0.0 [3] bonsai_0.1.0 [4] rules_1.0.0 [5] finetune_0.2.0 [6] yardstick_1.0.0 [7] workflowsets_1.0.0 [8] workflows_1.0.0 [9] tune_1.0.0 [10] tibble_3.1.7 [11] rsample_1.0.0 [12] recipes_1.0.1 [13] purrr_0.3.4 [14] parsnip_1.0.0 [15] modeldata_1.0.0 [16] infer_1.0.2 [17] dials_1.0.0 [18] scales_1.2.0 [19] broom_1.0.0 [20] tidymodels_1.0.0 [21] ggplot2_3.3.6 [22] rnaturalearth_0.1.0 [23] sf_1.0-8 [24] terra_1.6-3 [25] lubridate_1.8.0 [26] stringr_1.4.0 [27] tidyr_1.2.0 [28] dplyr_1.0.9 [29] pacman_0.5.1
Keywords: global water flux partitioning; runoff; evapotranspiration; precipitation; machine learning; shapley values; area of applicability; dissimilarity index; Computer Sciences; Datavetenskap (datalogi)